2022
DOI: 10.1101/2022.08.31.506019
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The core effector RipE1 ofRalstonia solanacearuminteracts with and cleaves Exo70B1 and is recognized by the Ptr1 immune receptor

Abstract: Ralstonia solanacearum depends on numerous virulence factors, also known as effectors, to promote disease in a wide range of economically important host-plants. Although some of these effectors have been characterized, none has been shown to target the host secretion machinery so far. Here, a screening was performed, using an extended library of NLR plant immune receptors integrated domains (IDs), to identify new effector targets. The results uncovered that the core effector RipE1, of the R. solanacearum speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 101 publications
(171 reference statements)
0
9
0
Order By: Relevance
“…As NbPtr1 is required for the recognition of effectors from different families, probably by monitoring the state of the plasma membrane-associated protein RIN4 (Ahn et al, 2022;Mazo-Molina et al, 2020), we next investigated RipE1 subcellular localization with laser scanning confocal microscopy. Nakano and Mukaihara (2019b) reported a nucleocytoplasmic localization for the N-terminally tagged RipE1 (from strain RS1000), while we and others (Jeon et al, 2020;Tsakiri et al, 2023) observed a plasma membrane localization for RipE1 C-terminally tagged with yellow fluorescent protein (YFP). This difference suggests that RipE1 association with the plasma membrane is mediated through the N-terminal region of the protein.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…As NbPtr1 is required for the recognition of effectors from different families, probably by monitoring the state of the plasma membrane-associated protein RIN4 (Ahn et al, 2022;Mazo-Molina et al, 2020), we next investigated RipE1 subcellular localization with laser scanning confocal microscopy. Nakano and Mukaihara (2019b) reported a nucleocytoplasmic localization for the N-terminally tagged RipE1 (from strain RS1000), while we and others (Jeon et al, 2020;Tsakiri et al, 2023) observed a plasma membrane localization for RipE1 C-terminally tagged with yellow fluorescent protein (YFP). This difference suggests that RipE1 association with the plasma membrane is mediated through the N-terminal region of the protein.…”
mentioning
confidence: 72%
“…The N-terminal region of RipE1 was not predicted to participate in the cysteine-protease fold in a predicted structural model (Tsakiri et al, 2023). This region does not contain a myristylation motif that was reported for several plasma membrane-associated T3S effectors, including AvrRpm1 (Nimchuk et al, 2000).…”
mentioning
confidence: 89%
“…The exocyst complex is a conserved octameric protein complex that regulates the tethering of secretion vesicles to the cell membrane (Mei & Guo, 2019). Being the components of an essential cellular mechanism, exocyst subunits are often targeted by pathogens that manipulate host cell physiology (Michalopoulou et al., 2022; Tsakiri et al., 2022; Wang et al., 2019). Successful plant pathogens use an arsenal of protein effectors, which display a variety of functions (Kotsaridis et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The AlphaFold database is currently vastly expanding, including additional proteomes and catalogued protein structures for even more accurate predictions. At the publication time, the AlphaFold source code is accessible online (Collabfold) and can be used to predict the protein structure of any protein of interest, as was done for the Ralstonia T3E RipE1 that harbors a cysteine protease domain (Tsakiri et al, 2022). More recently, the algorithm AlphaFold-Multimer has been created that could be used for the modelling of (effector-host protein) interactions (Evans et al, 2021).…”
Section: Generating a Facial Composite: T3e And T3e-host Complexed Pr...mentioning
confidence: 99%